2004
DOI: 10.1021/la0356349
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Contact Formation for Molecular Electronics:  Interactions between Vapor-Deposited Metals and Self-Assembled Monolayers of Conjugated Mono- and Dithiols

Abstract: We present grazing-incidence Fourier transform infrared and AFM data of Au, Al, and Ti vapor-deposited onto self-assembled monolayers (SAMs) of conjugated mono- and dithiols. SAMs of 4,4'''-dimercapto-p-quaterphenyl, 4,4"-dimercapto-p-terphenyl, and 4,4'-dimercapto-p-biphenyl have reactive thiols at the SAM/vacuum interface that interact with vapor-deposited Au or Al atoms, preventing metal penetration. Conjugated monothiols lack such metal blocking groups, and metals (Au, Al) can penetrate into their SAMs. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
237
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(249 citation statements)
references
References 38 publications
12
237
0
Order By: Relevance
“…To do that, we deposited 3 nm of Ag on top of the SAM and measured by FTIR in an attenuated total reflection configuration the absorption of the SAM. 44 The coincidence of the characteristic stretching frequencies for COO-, CH 2 and CH 3 suggest that the SAM has not been substantially modified after the first steps of electrode deposition (Fig. 2).…”
Section: Sams To Passivate the Metal-semiconductor Interfacementioning
confidence: 90%
See 1 more Smart Citation
“…To do that, we deposited 3 nm of Ag on top of the SAM and measured by FTIR in an attenuated total reflection configuration the absorption of the SAM. 44 The coincidence of the characteristic stretching frequencies for COO-, CH 2 and CH 3 suggest that the SAM has not been substantially modified after the first steps of electrode deposition (Fig. 2).…”
Section: Sams To Passivate the Metal-semiconductor Interfacementioning
confidence: 90%
“…After substrate functionalization the most critical step in the fabrication of SAMs junctions is the deposition of the top electrode, as it can compromise the integrity of the underlying molecular layer. The influence of the deposition conditions has been widely studied in other systems, 28,[40][41][42][43] and soft-electrode transfer or indirect evaporation reported as the less harming methods to the SAM. In our case we have also found that direct metal evaporation is capable of maintaining the quality SAMs for low enough deposition rates and temperatures (see Experimental section for more details).…”
Section: Sams To Passivate the Metal-semiconductor Interfacementioning
confidence: 99%
“…also Section 7.2, below). [34,67,69,70,92,[94][95][96] Beyond structure and morphology, several surface analyses, mainly spectroscopic ones, can provide information on the electronic structure of the system. As such information cannot be extracted directly from the transport data, the use of complementary methods is crucial for understanding transport mechanisms.…”
Section: Monolayer Characterizationmentioning
confidence: 99%
“…[67,69,70,92,[94][95][96]187] Evaporated Au or Cu on CH 3 ÀSi(111) interacts with the Si to form SiAu 3 or SiCu 3 , which detach the molecules from the surface. [67] Similarly, a monolayer of C 18 ÀSi(111) is generally destroyed by evaporation of Au or Ti, but not of Ag because of their different reactivity toward Si.…”
Section: Sources Of Defects and How To Avoid Themmentioning
confidence: 99%
“…In this geometry, a Au substrate usually serves as a bottom electrode. The top electrode could be metal nanoclusters prepared by vacuum vapor deposition [1][2][3][4][5][6][7][8][9][10] or from a suspension of metal nanoparticles. [11][12][13][14] Previous studies have shown that vapor-deposited Au or Ag penetrates into the SAM and inserts into the thiol-Au bond at the Au/ SAM interface when it is vacuum-deposited on an alkanethiol SAM with a methyl end group.…”
Section: Introductionmentioning
confidence: 99%